2023
DOI: 10.1088/1361-6560/acb2ae
|View full text |Cite
|
Sign up to set email alerts
|

Single pulse protoacoustic range verification using a clinical synchrocyclotron

Abstract: Objective: Proton therapy as the next generation radiation-based cancer therapy offers dominant advantages over conventional radiation therapy due to the utilization of the Bragg peak; however, range uncertainty in beam delivery substantially mitigates the advantages of proton therapy. This work reports using protoacoustic measurements to determine the location of proton Bragg peak deposition within a water phantom in real time during beam delivery. Approach: In protoacoustics, proton beams have a definitive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The comparability with the cited studies is only valid to a limited extent due to differences in the experimental design. In particular, it must be mentioned that the studies (Sueyasu et al 2022) and (Caron et al 2023) both use a water phantom and a substantially higher beam current (more than 4-fold) than in this study. It has already been shown that a higher instantaneous beam current contributes to a higher SNR at the same number of protons or dose (Schauer et al 2022), respectively.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The comparability with the cited studies is only valid to a limited extent due to differences in the experimental design. In particular, it must be mentioned that the studies (Sueyasu et al 2022) and (Caron et al 2023) both use a water phantom and a substantially higher beam current (more than 4-fold) than in this study. It has already been shown that a higher instantaneous beam current contributes to a higher SNR at the same number of protons or dose (Schauer et al 2022), respectively.…”
mentioning
confidence: 94%
“…Analysing the time of flight of the ionoacoustic signal propagation allows conclusions to be drawn about the position of the Bragg peak. Since the ionoacoustic signal is typically very noisy at clinically relevant doses, the signals are often averaged and filtered with analogue and digital filters such as band-pass filters, SavitzkyGolay filters (Caron et al 2023) or wavelet filters (Vallicelli et al 2021). From the time dependent ionoacoustic signal the location and the shape of the dose deposition can in theory be retrieved using a deconvolution procedure, however as deconvolution is a noise-sensitive process, this method is limited to high quality signals.…”
Section: Introduction and Purposementioning
confidence: 99%
See 1 more Smart Citation
“…For pulsed clinical proton machines ($100-250 MeV protons and $ls pulse duration), generation and sensing of protoacoustic waves has been reported by several groups across the globe. 28,30,46 Protoacoustic signals generated from $20 MeV protons with 200 ns pulse duration have also been reported. 47 Laser-driven proton beams are known to have the pulse durations of a few picoseconds [43][44][45] and are expected to be more suitable for PrAM as they easily satisfy the stress and thermal confinement conditions.…”
mentioning
confidence: 96%
“…When pulsed proton radiation is absorbed by tissues, it triggers the generation of protoacoustic waves resulting from the thermoelastic expansion of the irradiated tissue. These protoacoustic waves have been detected by numerous research groups worldwide [28][29][30][31][32] and are now being employed for on-line range verification and dose monitoring during the treatment. The propagation of protoacoustic waves in an acoustically homogeneous medium follows the acoustic wave propagation equation, 33…”
mentioning
confidence: 99%